ORIENTASI DAN EPISTEMOLOGI PEMIKIRAN PENDIDIKAN ISLAM PADA LEVEL DOKTORAL - Roby Setyawan; Khairunnas Rajab (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the orientation and epistemology of Islamic educational thought at the doctoral level, emphasizing the essential integration of revelation and reason as both sources and tools for acquiring knowledge. Unlike Western epistemology, which mainly emphasizes rationalism and empiricism, Islamic epistemology acknowledges revelation as the primary source alongside rational and experiential knowledge. This holistic framework underpins the philosophy and methodology of Islamic education, aiming to develop scholars who are not only intellectually proficient but also spiritually grounded according to the paradigm of tauhid. The research discusses the distinctiveness and profundity of doctoral-level Islamic education, which requires a balanced blend of traditional Islamic scientific methods and modern academic rigor. It further addresses the implications of this epistemological foundation on curriculum development, teaching methods, and educational policy in Islamic higher education. The study also explores the challenges posed by secular paradigms and the necessity for innovative, interdisciplinary, and technology-integrated approaches to foster the development of authentic Islamic knowledge and leadership. Ultimately, this study contributes to building an epistemological framework that nurtures intellectual excellence and moral integrity in Islamic education in contemporary global contexts.